The moderns : Midcentury American graphic design - Heller, Steven; D'Onofrio, Greg (Abrams, 2017)
In The Moderns, we meet the men and women who invented and shaped Mid-Century Modern graphic design in America. The book is made up of generously illustrated profiles, many based on interviews, of almost sixty designers whose magazine, book, and record covers; advertisements and package designs; posters; and other projects created the new world of postwar modernity. Some were émigrés from Europe; others were homegrown--all were intoxicated by elemental typography, primary colours, photography, and geometric or biomorphic forms. Some are well-known, others are honored in this volume for the first time, and together they comprised a movement that changed our world.